The Analysis of Southeast Asia's Tax Revenue Determinants (Empirical Study 2001–2021) - EP, Risda Liestianti; Ahmar, Nurmala; Darmansyah, Darmansyah (PT FORMOSA CENDEKIA GLOBAL, 2024)
The impact of Southeast Asian tax revenue factors on development capital is examined in this study. The aim of the research was to investigate the potential impact of tax revenue factors in the Southeast Asian region. samples and populations from ten Southeast Asian nations: Singapore, Malaysia, Indonesia, Brunei Darussalam, Philippines, Thailand, Vietnam, Laos, Cambodia, Myanmar, and Timor Leste. The study employs time series data spanning from 2001 to 2021. The PLS Structural Equation Modeling (SEM) data analysis technique is used in this work to analyze quantitative data. The study's findings indicate that while external debt has a negative impact on tax collection, per capita income and GDP manufacturing have a beneficial impact. In the meanwhile, tax revenue is unaffected by GDP agriculture, foreign direct investment, or corruption.